Land Tenure Planning in Order to Develop Territories of Traditional Natural Resource Use: Experience of Canada - A. V. Novikov (Plekhanov Russian University of Economics, 2021)
The article studies issues of land tenure planning for implementation of projects aimed at industrial development of the Arctic. Using the example of Northern provinces of Canada it shows evolution of land tenure strategic planning, analyzes its role in social and economic development of the territory. It is shown that involvement of aboriginal people of the North in the process of planning the use of land, forest and other natural resources can lower conflicts among land users, mining companies and the local population, protect territories of traditional land tenure in places of residence and traditional natural resource use of aborigine people and create necessary conditions for the development of traditional types of activity and sustainable space development of the Arctic. Canadian experience of land tenure planning in development of Arctic territories in the area of aboriginal people residence can be used in the Arctic zone of the Russian Federation to balance interests of concerned parties, i.e. local bodies of power, business and aboriginal people of the North.